Adaptation Atomic Design Method for Rapid Game Development Model - Rickman Roedavan; Agus Pratondo; Bambang Pudjoatmodjo; Yahdi Siradj (IJAIT (International Journal of Applied Information Technology), 2021)
Prototyping a game is a process to build the core game mechanics for use in the final game. This process is essential because it can save cost, time and reduce the potential for errors. There is a lot of study and research on the Game Development Life Cycle (GDLC). Some existing GDLC's were developed based on the waterfall model, while others were developed based on prototyping models. However, most of these models are not considered the cost and time factor. This research proposes a new Rapid Game Development (RGD) model, adapted from our previous work in developing the Game Mechanic Framework for Unity Game Engine. The experiment result showed that this method could be used to create a game faster while keeping the budget in mind during the development process.